PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING DALAM MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR IPA KELAS V DI UPTD SDN 109 INPRES LEKOALA KECAMATAN MAROS BARU KABUPATEN MAROS - utami, putri; Maulidnawati, Abrina; Irviana, Ira (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2023)
This study aims to find out (1) to find out how the Discovery Learning model is applied in class V (2) to find out the increase in creativity of class V students (3) to find out the learning outcomes of fifth grade students at SDN 109 Inpres Lekoala Maros. This study uses Classroom Action Research (CAR). The research object is the fifth grade students of SDN 109 Inpres Lekoala Maros. Data analysis in this study is observation, questionnaires, tests and documentation. The data in this study were analyzed using descriptive quantitative statistics. The results of the research carried out showed that (1) the application of the discovery learning model in science learning increased from the observations of teachers and students (2) the creativity questionnaire was distributed, the results in cycle I found an average value of 52.55% was stated to be less creative while in cycle II it is known that the average value of 80.30% is declared creative. (3) student learning outcomes in cycle I showed that the percentage of students whose grades were above the KKM only reached 52.25% so that they had not been able to reach the research success criteria. In cycle II the percentage of student scores above the KKM increased to 85%. Based on the results of the research and discussion, it can be concluded that the Discovery Learning learning model can increase creativity and science learning outcomes at SDN 109 Inpres Lekoala Maros.